A Quasi Experimental Study: Cultivating Mathematical Resilience via Intervention in Chinese classrooms - Wang Xia, Madihie; Amalia, Madihie (Frontiers Media SA, 2026)
Introduction: This study evaluates the efficacy of a culturally adapted Chinese Resilience Intervention Module in enhancing mathematical resilience among university students, grounded in the Sidek resilience framework.